THE EFFECT OF TOTAL QUALITY MANAGEMENT IMPLEMENTATION ON QUALITY CULTURE AT PT LONDON SUMATRA - Amalia Trihapsari; Juniarti; Ameliya Adisty; Anita Br Sinambela; Fara Dhia Naaura (Universitas Efarina, 2022)
This study aims to determine the influence between total quality management on the quality culture of case studies at PT London Sumatera-Medan. The research approach carried out in this study is associative / quantitative. The population of this study is managers and employees of PT London Sumatera-Medan totaling 40 people. The sampling method used is census i.e., making the entire population a sample in this study. So that the number of samples is 40 respondents. The analysis method used in writing this thesis is an analysis technique with a simple linear regression method with SPSS software application tools. The results showed that Total Quality Management has a positive and significant effect on Quality Culture.